Lyelliceratidae and Flickiidae (Ammonoidea) from the Upper Albian of the Helvetic Shelf (western Alps, France and Switzerland) - Kennedy, W; Delamette, M (1994)
The condensed Upper Albian to Lower Cenomanian deposits of the Helvetic Shelf of France and Swtizerland yield diverse ammonite fauna includings representatives of the family Lyelliceratidae, subfamily Stoliczkaiinae that is the origin of the Upper Cretaceous Acanthoceratidae and its descendants, as well as representatives of the dwarf stoliczkaiine offshoot, the family Flickiidae, subfamily Salaziceratinae. -from Authors